Vesical calculus associated with vesicovaginal fistula - Ming-Huei Cheng; Hsiang-Tai Chao; Huann-Cheng Horng; Man-Jung Hung; Ben-Shian Huang; Peng-Hui Wang (Wolters Kluwer Medknow Publications, 2014)
Vesicovaginal fistula (VVF) is relatively common after radiotherapy, but the formation of a bladder stone after VVF is still rare. The diagnosis is often delayed, and mortality sometimes occurs with delayed diagnosis and treatment, especially in elderly and disabled women. To increase knowledge of this unusual condition-vesical stone associated with VVF-we present a case report, and summarize the published cases to review this topic, focusing on the etiology, symptoms and signs, and recent management strategy. Finally, based on this case report, we emphasize that careful physical examination and the use of less invasive and economic tools, such as plain X-ray are important to investigate this very sick and old lady, because these strategies could help us to make an accurate diagnosis earlier without the need for more aggressive, invasive, and expensive tools.